Проблеми культурного поділу неоліту Волинського та Києво-Житомирського Полісся - Переверзєв, С.В. (Інститут археології НАН України, 2008)
У статті розглядаються проблемні питання культурної диференціації ранньонеолітичних пам’яток Південного Полісся. Аналізуються критерії виділення археологічних культур раннього неоліту. Робиться висновок про необгрунтованість існування поняття волинської неолітичної культури, обгрунтовується необхідність вживання поняття «керамічний етап яніславицької культури» як складової частини дніпро-донецької культурно-історичної області. In article the complicated questions of cultural differentiation of Early Neolithic sites of Northwest Polesye of Ukraine are revealed. Allocation criteria of archaeological cultures of the Early Neolithic are analyzed. The conclusion about groundlessness of existence of concepts of Volyn Neolithic Culture is made, necessity of the use of concept «the ceramic stage of Yanislavitsa culture» as a part of Dneper-Donets cultural-historical area is proved.